The Impact of ESG Disclosure, Intangible Assets, and IOS on Company Performance - Sinta Hen Maulita; Luciana Spica Almilia (University of Merdeka Malang, 2026)
This study was conducted to understand the effect of environmental disclosure, social disclosure, governance disclosure, intangible assets, and investment opportunity set on the performance of companies listed on the BGK Foundation and the Indonesia Stock Exchange (IDX) during the period 2019-2023. A total of 413 data points were used as samples. Environmental Disclosure, Social Disclosure, and Governance Disclosure data were obtained from the BGK Foundation website by considering 11 indicators in each aspect. Intangible assets were measured using the intangible asset value (INTAV) formula, and Investment Opportunity Set was measured using the Market to Book Value of Equity (MBVEBVE) ratio, while company performance was measured using the Return on Assets (ROA) ratio. This study is a quantitative study using secondary data in the form of ESG disclosure data available on the BGK Foundation website and company annual reports. Data analysis techniques used multiple linear regression analysis. The results of this study indicate that environmental disclosure and investment opportunity set affect company performance. On the other hand, social disclosure, governance disclosure, and intangible assets do not affect company performance.